Implementasi Black Box Testing pada website E-commerce Shopee menggunakan State Transition Testing - Salim, Alissa; Rusdiansyah, Rusdiansyah (Institut Bisnis dan Informatika Kwik Kian Gie, 2024)
A website must undergo software testing before it is used or published to the pub-lic. There are two general testing methods: white box testing and black box test-ing. In this article, the black box testing method is chosen, which is a testing method focused on the functionality of the application without looking into the internal code structure. Several testing techniques in the black box testing method include equivalence partitioning testing, boundary value analysis testing, compar-ison testing, and others.In this article, the author implements the state transition technique on the e-commerce website Shopee. State Transition testing is a tech-nique or method that focuses on testing the behavior of the system when transi-tioning from one state or mode to another. The goal is to ensure that the transi-tions between these states or modes work according to the specified require-ments.The testing process begins with identifying the states or modes present in the system to be tested. The second step is creating a transition diagram or state transition diagram that depicts the relationship between the occurring modes. The third step is determining the test cases that cover all the occurring transitions, and the final step is analyzing the test results.By using state transition testing, it is possible to test and validate the system's behavior when transitioning between states with comprehensive coverage, ensuring that the Shopee e-commerce website functions properly in various user scenarios.